Potret Seorang Mufassir Tabi’in: Mujahid bin Jabir dan Kitab Tafsirnya - Rochimah, Nazilatur; Nabil Maghfuri; Yuliana Desi Rahmawati (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2024)
Interpretation of the Qur'an has become an integral part of Islamic history, starting from the time of the Prophet Muhammad, his companions, tabi'in, and so on until today. This interpretive process continues to develop from one generation to the next, both in terms of the interpretive sources used, the interpretive methods applied, and the interpretive styles that emerge. Each generation has its own characteristics in interpreting the Qur'an, and during the Tabi'in era, this interpretation was based on the Qur'an, the hadith of the Prophet, the history of the Companions, the traditions of the people of the book, and the ijtihad of ulama. This article focuses on a prominent mufassir from the tabi'in period, namely Mujahid bin Jabar. He is a scholar who has a very good reputation thanks to the breadth of his knowledge in various fields such as tafsir, hadith, fiqh, and qiraat. Apart from that, Mujahid was also known as one of the students who had a sanad that was well connected to the Prophet's friend, Ibnu Abbas. In this research, qualitative methods with a literature review approach were used to explore information regarding sources, methods and interpretive styles in Mujahid bin Jabar's tafsir works. The information obtained was analyzed to understand Mujahid's contribution to the tradition of interpreting the Koran and its impact on understanding Islam. Some of the main findings that the author managed to reveal include that Mujahid's interpretation contributes to making it easier for readers because the contents of the interpretation are easy to understand, clear and not long-winded and directly lead to the main points being interpreted. Apart from that, the historical sources used by Mujahid in the interpretation process can also be accounted for because Mujahid is one of the figures closest to his friends so the authenticity of his narration is guaranteed. However, Mujahid's interpretation also has shortcomings in the form of not interpreting the verses in their entirety but only part of the verses of the Koran which he thinks are important to interpret.